FAILURE MODE ANALYSIS AND CRITICALITY ANALYSIS FOR DETERMINING THE HEALTH INDEX OF DISTRIBUTED CONTROL SYSTEM EQUIPMENT IN PLTU - Saputra Dwi Nugroho (TRAKSI, 2023)
A steam power plant (PLTU) is a power plant that uses coal fuel in its function to produce electrical energy. The main equipment of PLTU includes boilers, turbines, generators, distributed control systems (DCS), transformers and common systems. PLTU as a power plant must maintain its reliability to meet the demands of financial performance and technical performance. One of the main generating equipment at PLTU Lampung that must be maintained for reliability is the distributed control system (DCS) which is the main controller of the power plant. to maintain the reliability of DCS equipment, Failure Mode, Effect and Criticality Analysis (FMECA) analysis was carried out, then the equipment health index was compiled so that the current condition of the PLTU Lampung Unit 2 DCS equipment was obtained. The equipment health index is very useful for determining preventive measures so that the DCS equipment does not experience a malfunction that caused PLTU Lampung Unit 2 to stop production. The research that has been carried out has obtained the health index of the DCS PLTU Lampung Unit 2 equipment of 98.35% with the health index value of the components below, namely FCS 106 = 95.3%, FCS 107 = 96.45%, FCS 108 = 100%, FCS 109 = 100% and FCS 110 = 100%.